Hukum Sebagai Pengendalian Sikap dan Perilaku Sosial - Mustafa, Mustafa; Maria, Chery; Yunus, Shalsya Malika; Sukardi, Alex; Budi, Raliyanto; Subroto, Agung; D Soge, Albertus; R P, Dharmasanti (Universitas Proklamasi 45, 2024)
Humans are social creatures who always fulfill physical needs and recognize their existence as social creatures so that their attitudes and behavior towards other people and their environment are within a system of rules. These certain customs are sustainable and bound by a sense of shared identity. Apart from that, the surrounding natural environment contributes and has a big influence on the formation of attitudes and behavior, as well as a person's character. Therefore, law is essential to regulate social interactions, to ensure the continuity of life, fundamental things are needed, namely justice and welfare, as a means to regulate, guarantee certainty, provide credibility, a means for the government to regulate and guarantee the continuity of life. Control is a means of distributing resources ensuring order and stability of society, and maintaining its existence to achieve benefits following the objectives of the law. People's social attitudes and behavior can be controlled by the laws in force in the country where the people live. With the existence of laws, people can live comfortably, peacefully, and safely.